ANALISIS GAYA BAHASA DALAM SLOGAN MAKANAN RINGAN DI PONTIANAK KALIMANTAN BARAT - Husen, Deary Pratama; Wartiningsih, Agus; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe role of slogans in presenting snacks is hoped to help consumers in always remembering the brand of the offered product. Slogans with good quality requires high creativity, because slogans require correct dictions and must be interesting. The purpose of this research is to find the language style used in snacks slogans and finding out the purpose of said slogans. This research is a qualitative descriptive research, by following the steps of collecting, sorting, clarifying, analyzing, and concluding. This research is a descriptive research because of the data obtained cannot be put to numbers. The finding of this research shows that the slogans that are found in snacks have the language style of hyperbole, metaphor, repetitive, and denotative meaning. Therefore, in one advertisement not only one style is found, multiple language styles can be found, this give the effect of reinforcement of meaning in influencing the interest of a snack product by using hyperbole and metaphor.Keywords: slogan, snack, language style, pontianak